Triatomines (Hemiptera, Reduviidae) blood intake: Physical constraints and biological adaptations. (February 2017) - Sant'Anna, Maurício Roberto Viana; Soares, Adriana Coelho; Araujo, Ricardo Nascimento; Gontijo, Nelder Figueiredo; Pereira, Marcos Horácio
Graphical abstract: Highlights: Triatomine bugs take blood directly from vessels of the host's skin. Blood viscosity interferes with cibarial pump operation of triatomines. R. prolixus releases saliva continuously throughout its blood feeding. Blood clotting in midgut environment affects the bug's feeding performance. Bioactive molecules both from saliva and midgut assist in insect's blood intake. Abstract: In order to efficiently obtain blood from their vertebrate hosts, bloodsucking arthropods have undergone an evolutionary selection process leading to specialist adaptations in their feeding apparatus (mouthparts and suction pumps) and salivary molecules. These adaptations act to counteract haemostasis, inflammation, and immune responses in their vertebrate hosts. The association of haematophagous arthropods with vertebrate hosts during a blood feed allows the transmission of pathogens between their hosts and vectors in a tripartite interaction. Feeding mechanisms in haematophagous arthropod species have been the subject of studies over at least eight decades worldwide, as a consequence of the importance of vector-borne diseases and their impact on human health. Here we review studies of the feeding mechanisms of triatomine bugs, with a particular focus on factors that influence their feeding performance when obtaining a blood meal from different vertebrate hosts.